Combining Preschool Teacher Training with Parenting Education : A Cluster-Randomized Controlled Trial - Ozler, Berk; Fernald, Lia C. H.; Kariger, Patricia; McConnell, Christin; Neuman, Michelle; Fraga, Eduardo (World Bank, Washington, DC, 2016)
This paper evaluates a government program in Malawi, which aimed to improve quality at community-based childcare centers and complemented these efforts with a group-based parenting support program. Children in the integrated intervention arm (teacher training and parenting) had significantly higher scores in measures of language and socio-emotional development than children in centers receiving teacher training alone at the 18-month follow-up. However, the study finds no effects on child assessments at the 36-month follow-up. Significant improvements at the centers relating to classroom organization and teacher behavior in the teacher-training only arm did not translate into improvements in child outcomes at either follow-up. The findings suggest that, in resource-poor settings with informal preschools, programs that integrate parenting support within preschools may be more effective than programs that simply improve classroom quality.